High-strength, high-conductivity, corrosion-resistant and antibacterial alloy film and preparation method thereof
By doping Ag elements into TiAlCrSi alloy films and preparing TiAlCrSiAg alloy films using magnetron sputtering technology, the problems of insufficient conductivity and antibacterial properties of traditional alloy films are solved, and a multifunctional material with high strength, corrosion resistance and antibacterial properties are realized.
Patent Information
- Application Number
- CN202411829010.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-12-12
AI Technical Summary
Traditional TiAlCrSi alloy films have insufficient performance in terms of electrical conductivity and antibacterial properties, making it difficult to meet the high-performance demand for multifunctional materials in modern industrial and high-tech fields.
Through magnetron sputtering technology, Ag elements are doped in TiAlCrSi alloy film to prepare a high-strength, high-conductivity, corrosion-resistant and antibacterial TiAlCrSiAg alloy film. This method ensures that the film has a significant improvement in electrical conductivity, corrosion resistance and antibacterial properties by precisely controlling the sputtering process parameters.
It achieves the film's conductivity and antibacterial properties while maintaining high strength and corrosion resistance, and provides a broader application prospect, especially in medical devices, electronic components and corrosion environments.
Smart Images

Figure CN119571252A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metal surface modification, and in particular to a high-strength, high-conductivity, corrosion-resistant and antibacterial alloy film and a preparation method thereof. Background Art
[0002] In modern industry and high-tech fields, the versatility and high performance requirements of materials are constantly increasing, especially in the electronics, medical, aerospace and other industries, where materials must not only have high strength and corrosion resistance, but also excellent electrical conductivity and antibacterial properties. Although traditional alloy materials perform well in some properties, it is difficult to meet the needs of modern multiple performance. Titanium aluminum chromium silicon (TiAlCrSi) alloy is widely used in the above fields due to its stability, corrosion resistance and good mechanical properties under high temperature conditions. However, the deficiencies of TiAlCrSi alloy in electrical conductivity and antibacterial properties limit its promotion in higher-end applications.
[0003] Silver (Ag) has attracted extensive attention in the field of materials science due to its unique physical and chemical properties, especially its excellent electrical conductivity and antibacterial properties. Incorporating Ag into alloys can significantly improve the electrical conductivity of the material and give it excellent antibacterial properties, making it more suitable for electronic devices, medical devices and environmentally demanding applications. However, uniformly incorporating Ag elements into alloy films while maintaining their structural integrity and versatility is a challenge in current material research and development.
[0004] Magnetron sputtering technology is an ideal choice for alloy film preparation because it can accurately control the composition and thickness of the film and achieve the preparation of high-quality films under low temperature conditions. At present, there is no report on the technology of doping Ag into TiAlCrSi alloy films by magnetron sputtering technology.
[0005] Therefore, it is urgent to develop a technology for preparing Ag-doped TiAlCrSi alloy films by magnetron sputtering, which has important research and application value for improving the overall performance of the material, extending its service life, and enhancing the safety and reliability of applied products. Summary of the invention
[0006] The purpose of the present invention is to provide a high-strength, high-conductivity, corrosion-resistant and antibacterial alloy film and a preparation method thereof. By using magnetron sputtering technology, Ag elements are doped into the TiAlCrSi alloy film, which can significantly improve its conductivity and antibacterial properties while ensuring the high strength and corrosion resistance of the film. Among them, Ag doping can not only enhance the electronic conductivity of the film, but also give the film surface a lasting antibacterial effect by releasing Ag ions. This multifunctional TiAlCrSiAg alloy film has broad application prospects in medical devices, electronic components and corrosive environments. The present invention well solves the problems of low hardness, poor corrosion resistance and antibacterial properties of traditional alloy films mentioned in the above background technology.
[0007] In order to achieve the above object, the present invention adopts the following technical solutions:
[0008] In a first aspect, the present invention provides a method for preparing a high-strength, high-conductivity, corrosion-resistant and antibacterial alloy film, comprising the following steps:
[0009] Step 1: The surface of the test piece substrate is polished, and then ultrasonically cleaned. The cleaning reagents are acetone, anhydrous ethanol, and deionized water in sequence, and then dried for use;
[0010] Step 2: Prepare four pure metal sector-shaped targets of Ti, Al, Cr and Si according to the required proportion of the components, and splice the various targets into a TiAlCrSi alloy target by means of target splicing;
[0011] Step 3: placing the test piece substrate processed in step 1 in a magnetron sputtering chamber of a magnetron sputtering device, installing the TiAlCrSi alloy target and the Ag target spliced in step 2 on corresponding target positions in the magnetron sputtering chamber, then evacuating the magnetron sputtering chamber, and then introducing argon gas into the magnetron sputtering chamber to perform ion etching on the surface of the test piece substrate;
[0012] Step 4: After the predetermined pressure is reached in the magnetron sputtering chamber, the TiAlCrSi alloy target is opened alone to deposit the coating for a period of time, and then the TiAlCrSi alloy target is closed and the Ag target is kept open; then the TiAlCrSi alloy target is opened at an interval to deposit the coating, and then the TiAlCrSi alloy target is closed, and the deposition coating is repeated several times, with the interval time decreasing successively, and finally the TiAlCrSi alloy target and the Ag target are closed to end the coating;
[0013] Step 5: After the coating is completed, wait for the magnetron sputtering chamber to cool to room temperature, take out the sample, and obtain a high-strength, high-conductivity, corrosion-resistant and antibacterial TiAlCrSiAg alloy film.
[0014] As a specific technical solution of the present invention, the thickness of the TiAlCrSiAg alloy film is 3.5 μm to 4.2 μm.
[0015] As a specific technical solution of the present invention, in step 1, the test piece substrate is any metal substrate of iron and its alloys. As an example, the test piece substrate can be a 304 stainless steel substrate.
[0016] As a specific technical solution of the present invention, in step 1, acetone, anhydrous ethanol and deionized water are used to ultrasonically clean the test piece substrate in sequence, and the cleaning time is 10 minutes to 15 minutes, and the drying temperature is 70 minutes to 80°C.
[0017] As a specific technical solution of the present invention, in step 2, the composition ratio of the TiAlCrSi alloy target is Ti:Al:Cr:Si=30:30:30:10, and the purity is not less than 99.90wt.%; in step 3, the purity of the Ag target is not less than 99.99wt.%. Specifically, the target splicing method is to splice Ti sheets, Al sheets, Cr sheets, Si sheets and Cr sheets with certain vertex angles.
[0018] As a specific technical solution of the present invention, in step 3, a direct current power supply is used for the TiAlCrSi alloy target, and a HiPIMS power supply is used for the Ag target.
[0019] As a specific technical solution of the present invention, in step 3, the magnetron sputtering chamber is evacuated to a vacuum degree of 1.8×10 -3 Pa~2.7×10 -3 Pa.
[0020] As a specific technical solution of the present invention, in step 3, when argon gas is introduced for ion etching, the flow rate of the introduced argon gas is 50 sccm to 60 sccm, the purity of the argon gas is above 99.99%, and the total duration of the ion etching is 10 minutes.
[0021] As a specific technical solution of the present invention, in step 4, the power of the TiAlCrSi alloy target is set to 200W-240W; the power of the Ag target is set to 400W-500W.
[0022] As a specific technical solution of the present invention, in step 4, the TiAlCrSi alloy target is first opened separately for deposition coating, and the deposition time is 70min to 100min; the Ag target is opened for an interval of 18min to 22min, and then the TiAlCrSi alloy target is opened, the power of the TiAlCrSi alloy target remains unchanged, the deposition time is 18min to 22min, and then the TiAlCrSi alloy target is closed; after an interval of 12min to 17min, the TiAlCrSi alloy target is opened again, the power of the TiAlCrSi alloy target remains unchanged, the deposition time is 12min to 17min, and then the TiAlCrSi alloy target is closed; after an interval of 8min to 11min, the TiAlCrSi alloy target is opened again, the power of the TiAlCrSi alloy target remains unchanged, the deposition time is 8min to 11min, and then the TiAlCrSi alloy target is closed; after an interval of 4min to 6min, the TiAlCrSi alloy target is opened again, the power of the TiAlCrSi alloy target remains unchanged, the deposition time is 4min to 6min, and then the TiAlCrSi alloy target is closed.
[0023] In a second aspect, the present invention also provides a high-strength, high-conductivity, corrosion-resistant and antibacterial alloy film prepared by the above-mentioned preparation method, and the high-strength, high-conductivity, corrosion-resistant and antibacterial alloy film is a TiAlCrSiAg alloy film.
[0024] Compared with the prior art, the present invention provides a high-strength, high-conductivity, corrosion-resistant and antibacterial alloy film and a preparation method thereof, which has the following beneficial effects:
[0025] The present invention provides a high-strength, high-conductivity, corrosion-resistant and antibacterial alloy film and a preparation method thereof. Ag element is doped into TiAlCrSi alloy by magnetron sputtering, and a TiAlCrSiAg alloy film is prepared on the surface of a stainless steel substrate by precisely controlling sputtering process parameters, thereby significantly improving the conductivity, corrosion resistance and antibacterial properties of the film. The film prepared by this method has a dense structure, good bonding effect with the substrate, excellent corrosion resistance and antibacterial ability, and a small reduction in hardness while maintaining a relatively high strength.
[0026] The preparation method of the present invention has simple process, easy operation and low cost. The high-strength, high-conductivity, corrosion-resistant and antibacterial alloy film prepared by the method can be used in electronic devices, micro-electromechanical systems, medical devices and other fields, and has the prospect of application in industrial fields and commercial production; at the same time, it also has important research and application value for improving the overall performance of materials, extending service life and enhancing the safety and reliability of application products. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0028] Figure 1 is a cross-sectional view of the TiAlCrSiAg alloy film in Example 1;
[0029] Figure 2 This is a light microscope image of the TiAlCrSiAg alloy film after scratch testing in Example 1;
[0030] Figure 3 The electrochemical polarization curves of the TiAlCrSiAg alloy films prepared in Examples 1 to 3 and Comparative Example 1;
[0031] Figure 4 The resistivity / hardness relationship diagram of the TiAlCrSiAg alloy films prepared in Examples 1 to 3 and Comparative Example 1;
[0032] Figure 5 This is a photo of the plate culture of Escherichia coli and Staphylococcus aureus on the TiAlCrSiAg alloy film in Example 1;
[0033] Figure 6 This is a bar graph showing the surface antibacterial rates of the TiAlCrSiAg alloy films prepared in Examples 1 to 3 and Comparative Example 1 when culturing Escherichia coli and Staphylococcus aureus on a flat plate. DETAILED DESCRIPTION
[0034] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0035] In the embodiments and comparative examples, the experimental methods used are conventional methods unless otherwise specified, the materials and reagents used are commercially available unless otherwise specified, and the equipment and instruments used are conventional prior art equipment and instruments unless otherwise specified.
[0036] The present invention is further described in detail below through detailed embodiments in conjunction with the accompanying drawings.
[0037] Example 1
[0038] This embodiment provides a high-strength, high-conductivity, corrosion-resistant and antibacterial TiAlCrSiAg alloy film, and the specific preparation method includes the following steps:
[0039] Step 1: Polish the surface of the 304 stainless steel substrate, and then place it in ultrasonic tanks filled with acetone, anhydrous ethanol, and deionized water for ultrasonic cleaning. The ultrasonic cleaning time in each ultrasonic tank is 12 minutes. Then use a hair dryer to dry it at a temperature of about 70°C for use.
[0040] Step 2: According to the required proportion of components, four pure metal fan-shaped targets of Ti, Al, Cr and Si are prepared, and various targets are spliced into a TiAlCrSi alloy target (with a purity of not less than 99.90wt.%) by means of target splicing, wherein the composition ratio of the TiAlCrSi alloy target is Ti:Al:Cr:Si=30:30:30:10.
[0041] Step 3: Place the 304 stainless steel substrate after polishing, cleaning and drying in step 1 in the magnetron sputtering chamber of the magnetron sputtering device, install the TiAlCrSi alloy target and Ag target (purity not less than 99.99wt.%) spliced in step 2 on the corresponding target positions in the magnetron sputtering chamber, the TiAlCrSi alloy target uses a DC power supply, and the Ag target uses a HiPIMS power supply; then turn on the heating device, and evacuate the magnetron sputtering chamber to a vacuum degree of 1.8×10 -3 Pa, and then high-purity argon gas (purity of more than 99.99%) is introduced into the magnetron sputtering chamber to perform ion etching on the surface of the 304 stainless steel substrate. The argon gas flow rate is 50 sccm and the ion etching time is 10 min.
[0042] Step 4: After the predetermined pressure is reached in the magnetron sputtering chamber, the TiAlCrSi alloy target is opened separately for deposition coating for 80 minutes, and the power of the TiAlCrSi alloy target is set to 200W. Then the TiAlCrSi alloy target is closed and the Ag target is continuously opened, and the power of the Ag target is set to 400W; after an interval of 20 minutes, the TiAlCrSi alloy target is opened, and the power of the TiAlCrSi alloy target is adjusted to 200W. After deposition coating for 20 minutes, the TiAlCrSi alloy target is closed; after an interval of 15 minutes, the TiAlCrSi alloy target is opened again. , the power of the TiAlCrSi alloy target was adjusted to 200 W, and the TiAlCrSi alloy target was turned off after 15 minutes of deposition coating; after an interval of 10 minutes, the TiAlCrSi alloy target was opened again, the power of the TiAlCrSi alloy target was adjusted to 200 W, and the TiAlCrSi alloy target was turned off after 10 minutes of deposition coating; after an interval of 5 minutes, the TiAlCrSi alloy target was opened again, the power of the TiAlCrSi alloy target was adjusted to 200 W, and the TiAlCrSi alloy target and Ag target were turned off after 5 minutes of deposition coating, and the coating was ended.
[0043] Step 5: After the coating is completed, wait for the magnetron sputtering chamber to cool to room temperature, take out the sample, and obtain a high-strength, high-conductivity, corrosion-resistant and antibacterial TiAlCrSiAg alloy film.
[0044] The prepared TiAlCrSiAg alloy film was subjected to the following tests and characterizations, and the results are shown below:
[0045] (1) The cross-sectional view of the TiAlCrSiAg alloy film is shown in Figure 2. Figure 1 As shown, it can be observed that the thickness of the film is 3.61 μm.
[0046] (2) The optical microscopy images of the prepared TiAlCrSiAg alloy film after scratch testing are shown in Figure 2. Figure 2 As shown, it can be observed that the film is well bonded to the substrate, with a bonding force of 22.49N.
[0047] (3) The electrochemical polarization curve of TiAlCrSiAg alloy film is shown in Figure 3 As shown, the corrosion current density of the film is 4.293×10 -7 A.
[0048] (4) The resistivity / hardness relationship diagram of TiAlCrSiAg alloy film is shown in Figure 4 As shown, the resistivity of the film is 0.81 μΩ / m and the hardness is 31.67 GPa.
[0049] (5) Photos of bacterial colony culture on TiAlCrSiAg alloy film Figure 5 As shown, the surface antibacterial rate bar graph is as follows Figure 6 As shown, its antibacterial rate is 45.6% (Escherichia coli) and 48.8% (Staphylococcus aureus).
[0050] Example 2
[0051] This embodiment provides a high-strength, high-conductivity, corrosion-resistant and antibacterial TiAlCrSiAg alloy film, and the specific preparation method includes the following steps:
[0052] Step 1: Polish the surface of the 304 stainless steel substrate, and then place it in ultrasonic tanks filled with acetone, anhydrous ethanol, and deionized water for ultrasonic cleaning. The ultrasonic cleaning time in each ultrasonic tank is 12 minutes. Then use a hair dryer to dry it at a temperature of about 70°C for use.
[0053] Step 2: According to the required proportion of components, four pure metal fan-shaped targets of Ti, Al, Cr and Si are prepared, and various targets are spliced into a TiAlCrSi alloy target (with a purity of not less than 99.90wt.%) by means of target splicing, wherein the composition ratio of the TiAlCrSi alloy target is Ti:Al:Cr:Si=30:30:30:10.
[0054] Step 3: Place the 304 stainless steel substrate after polishing, cleaning and drying in step 1 in the magnetron sputtering chamber of the magnetron sputtering device, install the TiAlCrSi alloy target and Ag target (purity not less than 99.99wt.%) spliced in step 2 on the corresponding target positions in the magnetron sputtering chamber, the TiAlCrSi alloy target uses a DC power supply, and the Ag target uses a HiPIMS power supply; then turn on the heating device, and evacuate the magnetron sputtering chamber to a vacuum degree of 1.8×10 -3 Pa, and then high-purity argon gas (purity of more than 99.99%) is introduced into the magnetron sputtering chamber to perform ion etching on the surface of the 304 stainless steel substrate. The argon gas flow rate is 50 sccm and the ion etching time is 10 min.
[0055] Step 4: After the predetermined pressure is reached in the magnetron sputtering chamber, the TiAlCrSi alloy target is opened separately for deposition coating for 80 minutes, and the power of the TiAlCrSi alloy target is set to 200W. Then the TiAlCrSi alloy target is closed and the Ag target is continuously opened, and the power of the Ag target is set to 450W; after an interval of 20 minutes, the TiAlCrSi alloy target is opened, and the power of the TiAlCrSi alloy target is adjusted to 200W. After deposition coating for 20 minutes, the TiAlCrSi alloy target is closed; after an interval of 15 minutes, the TiAlCrSi alloy target is opened again. , the power of the TiAlCrSi alloy target was adjusted to 200 W, and the TiAlCrSi alloy target was turned off after 15 minutes of deposition coating; after an interval of 10 minutes, the TiAlCrSi alloy target was opened again, the power of the TiAlCrSi alloy target was adjusted to 200 W, and the TiAlCrSi alloy target was turned off after 10 minutes of deposition coating; after an interval of 5 minutes, the TiAlCrSi alloy target was opened again, the power of the TiAlCrSi alloy target was adjusted to 200 W, and the TiAlCrSi alloy target and Ag target were turned off after 5 minutes of deposition coating, and the coating was ended.
[0056] Step 5: After the coating is completed, wait for the magnetron sputtering chamber to cool to room temperature, take out the sample, and obtain a high-strength, high-conductivity, corrosion-resistant and antibacterial TiAlCrSiAg alloy film.
[0057] The prepared TiAlCrSiAg alloy film was subjected to the following tests and characterizations, and the results are shown below:
[0058] (1) The cross-sectional view of the TiAlCrSiAg alloy film is similar Figure 1 As shown, it can be observed that the thickness of the film is 3.76 μm.
[0059] (2) The optical microscopy images of the prepared TiAlCrSiAg alloy film after scratch testing are similar to Figure 2 As shown, it can be observed that the film is well bonded to the substrate, with a bonding force of 20.71N.
[0060] (3) The electrochemical polarization curve of TiAlCrSiAg alloy film is shown in Figure 3 As shown, the corrosion current density of the film is 4.090×10 -7 A.
[0061] (4) The resistivity / hardness relationship diagram of TiAlCrSiAg alloy film is shown in Figure 4 As shown, the resistivity of the film is 0.42 μΩ / m and the hardness is 29.93 GPa.
[0062] (5) The bacterial colony plate culture photos of TiAlCrSiAg alloy film are similar Figure 5 As shown, the surface antibacterial rate bar graph is as follows Figure 6 As shown, its antibacterial rate is 77.3% (Escherichia coli) and 81.1% (Staphylococcus aureus).
[0063] Example 3
[0064] This embodiment provides a high-strength, high-conductivity, corrosion-resistant and antibacterial TiAlCrSiAg alloy film, and the specific preparation method includes the following steps:
[0065] Step 1: Polish the surface of the 304 stainless steel substrate, and then place it in ultrasonic tanks filled with acetone, anhydrous ethanol, and deionized water for ultrasonic cleaning. The ultrasonic cleaning time in each ultrasonic tank is 12 minutes. Then use a hair dryer to dry it at a temperature of about 70°C for use.
[0066] Step 2: According to the required proportion of components, four pure metal fan-shaped targets of Ti, Al, Cr and Si are prepared, and various targets are spliced into a TiAlCrSi alloy target (with a purity of not less than 99.90wt.%) by means of target splicing, wherein the composition ratio of the TiAlCrSi alloy target is Ti:Al:Cr:Si=30:30:30:10.
[0067] Step 3: Place the 304 stainless steel substrate after polishing, cleaning and drying in step 1 in the magnetron sputtering chamber of the magnetron sputtering device, install the TiAlCrSi alloy target and Ag target (purity not less than 99.99wt.%) spliced in step 2 on the corresponding target positions in the magnetron sputtering chamber, the TiAlCrSi alloy target uses a DC power supply, and the Ag target uses a HiPIMS power supply; then turn on the heating device, and evacuate the magnetron sputtering chamber to a vacuum degree of 1.8×10 -3 Pa, and then high-purity argon gas (purity of more than 99.99%) is introduced into the magnetron sputtering chamber to perform ion etching on the surface of the 304 stainless steel substrate. The argon gas flow rate is 50 sccm and the ion etching time is 10 min.
[0068] Step 4: After the predetermined pressure is reached in the magnetron sputtering chamber, the TiAlCrSi alloy target is opened separately for deposition coating for 80 minutes, and the power of the TiAlCrSi alloy target is set to 200W. Then the TiAlCrSi alloy target is closed and the Ag target is continuously opened, and the power of the Ag target is set to 500W; after an interval of 20 minutes, the TiAlCrSi alloy target is opened, and the power of the TiAlCrSi alloy target is adjusted to 200W. After deposition coating for 20 minutes, the TiAlCrSi alloy target is closed; after an interval of 15 minutes, the TiAlCrSi alloy target is opened again. , the power of the TiAlCrSi alloy target was adjusted to 200 W, and the TiAlCrSi alloy target was turned off after 15 minutes of deposition coating; after an interval of 10 minutes, the TiAlCrSi alloy target was opened again, the power of the TiAlCrSi alloy target was adjusted to 200 W, and the TiAlCrSi alloy target was turned off after 10 minutes of deposition coating; after an interval of 5 minutes, the TiAlCrSi alloy target was opened again, the power of the TiAlCrSi alloy target was adjusted to 200 W, and the TiAlCrSi alloy target and Ag target were turned off after 5 minutes of deposition coating, and the coating was ended.
[0069] Step 5: After the coating is completed, wait for the magnetron sputtering chamber to cool to room temperature, take out the sample, and obtain a high-strength, high-conductivity, corrosion-resistant and antibacterial TiAlCrSiAg alloy film.
[0070] The prepared TiAlCrSiAg alloy film was subjected to the following tests and characterizations, and the results are shown below:
[0071] (1) The cross-sectional view of the TiAlCrSiAg alloy film is similar Figure 1 As shown, it can be observed that the thickness of the film is 3.88 μm.
[0072] (2) The optical microscopy images of the prepared TiAlCrSiAg alloy film after scratch testing are similar to Figure 2 As shown, it can be observed that the film is well bonded to the substrate, with a bonding force of 20.15N.
[0073] (3) The electrochemical polarization curve of TiAlCrSiAg alloy film is shown in Figure 3 As shown, the corrosion current density of the film is 3.478×10 -7 A.
[0074] (4) The resistivity / hardness relationship diagram of TiAlCrSiAg alloy film is shown in Figure 4 As shown, the resistivity of the film is 0.12 μΩ / m and the hardness is 25.78 GPa.
[0075] (5) The bacterial colony plate culture photos of TiAlCrSiAg alloy film are similar Figure 5 As shown, the surface antibacterial rate bar graph is as follows Figure 6 As shown, its antibacterial rate is 98.7% (Escherichia coli) and 96.9% (Staphylococcus aureus).
[0076] Comparative Example 1
[0077] This comparative example provides a TiAlCrSi alloy film, and the specific preparation method includes the following steps:
[0078] Step 1: Polish the surface of the 304 stainless steel substrate, and then place it in ultrasonic tanks filled with acetone, anhydrous ethanol, and deionized water for ultrasonic cleaning. The ultrasonic cleaning time in each ultrasonic tank is 12 minutes. Then use a hair dryer to dry it at a temperature of about 70°C for use.
[0079] Step 2: According to the required proportion of components, four pure metal fan-shaped targets of Ti, Al, Cr and Si are prepared, and various targets are spliced into a TiAlCrSi alloy target (with a purity of not less than 99.90wt.%) by means of target splicing, wherein the composition ratio of the TiAlCrSi alloy target is Ti:Al:Cr:Si=30:30:30:10.
[0080] Step 3: Place the 304 stainless steel substrate after polishing, cleaning and drying in step 1 in the magnetron sputtering chamber of the magnetron sputtering device, install the TiAlCrSi alloy target and Ag target (purity not less than 99.99wt.%) spliced in step 2 on the corresponding target positions in the magnetron sputtering chamber, the TiAlCrSi alloy target uses a DC power supply, and the Ag target uses a HiPIMS power supply; then turn on the heating device, and evacuate the magnetron sputtering chamber to a vacuum degree of 1.8×10 -3 Pa, and then high-purity argon gas (purity of more than 99.99%) is introduced into the magnetron sputtering chamber to perform ion etching on the surface of the 304 stainless steel substrate. The argon gas flow rate is 50 sccm and the ion etching time is 10 min.
[0081] Step 4: After the predetermined pressure is reached in the magnetron sputtering chamber, the TiAlCrSi alloy target is opened alone to deposit the coating for 180 minutes, and the power of the TiAlCrSi alloy target is set to 200W. Then the TiAlCrSi alloy target is closed to end the coating.
[0082] Step 5: After the coating is completed, after the magnetron sputtering chamber is cooled to room temperature, the sample is taken out to obtain a TiAlCrSi alloy film.
[0083] The prepared TiAlCrSi alloy film was subjected to the following tests and characterizations, and the results are shown below:
[0084] (1) The cross-sectional view of the TiAlCrSi alloy film is similar Figure 1 As shown, it can be observed that the thickness of the film is 3.86 μm.
[0085] (2) The optical microscopy images of the prepared TiAlCrSi alloy film after scratch testing are similar to Figure 2 As shown, it can be observed that the film is well bonded to the substrate, with a bonding force of 23.19N.
[0086] (3) The electrochemical polarization curve of TiAlCrSi alloy film is shown in Figure 3 As shown, the corrosion current density of the film is 7.762×10 -6 A.
[0087] (4) The resistivity / hardness relationship diagram of TiAlCrSi alloy film is shown in Figure 4 As shown, the resistivity of the film is 2.54 μΩ / m and the hardness is 33.15 GPa.
[0088] (5) The bacterial colony plate culture photos of TiAlCrSi alloy film are similar Figure 5 As shown, the surface antibacterial rate bar graph is as follows Figure 6 As shown, its antibacterial rate is 5.7% (Escherichia coli) and 6.4% (Staphylococcus aureus).
[0089] The above embodiments are merely illustrative of the concept and technical solution of the present invention, and are not intended to limit the present invention. Anyone familiar with the technology may modify or change the above embodiments without violating the spirit and scope of the present invention. Therefore, all equivalent modifications or changes made by a person with ordinary knowledge in the technical field without departing from the spirit and technical ideas disclosed by the present invention should still be covered by the claims of the present invention.
[0090] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This narrative method of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each implementation mode may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A method for preparing a high-strength, high-conductivity, corrosion-resistant and antibacterial alloy film, characterized in that: The following steps are involved: Step 1: The surface of the test piece substrate is polished, and then ultrasonically cleaned. The cleaning reagents are acetone, anhydrous ethanol, and deionized water in sequence, and then dried for use; Step 2: Prepare four pure metal sector-shaped targets of Ti, Al, Cr and Si according to the required proportion of the components, and splice the various targets into a TiAlCrSi alloy target by means of target splicing; Step 3: placing the test piece substrate processed in step 1 in a magnetron sputtering chamber of a magnetron sputtering device, installing the TiAlCrSi alloy target and the Ag target spliced in step 2 on corresponding target positions in the magnetron sputtering chamber, then evacuating the magnetron sputtering chamber, and then introducing argon gas into the magnetron sputtering chamber to perform ion etching on the surface of the test piece substrate; Step 4: After the predetermined pressure is reached in the magnetron sputtering chamber, the TiAlCrSi alloy target is opened alone to deposit the coating for a period of time, and then the TiAlCrSi alloy target is closed and the Ag target is kept open; then the TiAlCrSi alloy target is opened at an interval to deposit the coating, and then the TiAlCrSi alloy target is closed, and the deposition coating is repeated several times, with the interval time decreasing successively, and finally the TiAlCrSi alloy target and the Ag target are closed to end the coating; Step 5: After the coating is completed, wait for the magnetron sputtering chamber to cool to room temperature, take out the sample, and obtain a high-strength, high-conductivity, corrosion-resistant and antibacterial TiAlCrSiAg alloy film.
2. The preparation method according to claim 1, characterized in that: The thickness of the TiAlCrSiAg alloy film is 3.5 μm to 4.2 μm.
3. The preparation method according to claim 1, characterized in that: In step 1, the test piece substrate is any metal substrate of iron and its alloys.
4. The preparation method according to claim 1, characterized in that: In step 1, acetone, anhydrous ethanol and deionized water are used to ultrasonically clean the test piece substrate in sequence, and the cleaning time is 10 minutes to 15 minutes. The temperature of the drying treatment is 70 minutes to 80°C.
5. The preparation method according to claim 1, characterized in that: In step 2, the composition ratio of the TiAlCrSi alloy target is Ti:Al:Cr:Si=30:30:30:10, and the purity is not less than 99.90wt.%; in step 3, the purity of the Ag target is not less than 99.99wt.%.
6. The preparation method according to claim 1, characterized in that: In step 3, the magnetron sputtering chamber is evacuated to a vacuum degree of 1.8×10 -3 Pa~2.7×10 -3 Pa.
7. The preparation method according to claim 1, characterized in that: In step 3, when argon gas is introduced for ion etching, the flow rate of the introduced argon gas is 50 sccm to 60 sccm, the purity of the argon gas is above 99.99%, and the total duration of the ion etching is 10 minutes.
8. The preparation method according to claim 1, characterized in that: In step 4, the power of the TiAlCrSi alloy target is set to 200W-240W; the power of the Ag target is set to 400W-500W.
9. The preparation method according to claim 1, characterized in that: In step 4, the TiAlCrSi alloy target is first opened separately for deposition coating, and the deposition time is 70min to 100min; the Ag target is opened for an interval of 18min to 22min, and then the TiAlCrSi alloy target is opened, the power of the TiAlCrSi alloy target remains unchanged, the deposition time is 18min to 22min, and then the TiAlCrSi alloy target is closed; after an interval of 12min to 17min, the TiAlCrSi alloy target is opened again, the power of the TiAlCrSi alloy target remains unchanged, the deposition time is 12min to 17min, and then the TiAlCrSi alloy target is closed; after an interval of 8min to 11min, the TiAlCrSi alloy target is opened again, the power of the TiAlCrSi alloy target remains unchanged, the deposition time is 8min to 11min, and then the TiAlCrSi alloy target is closed; after an interval of 4min to 6min, the TiAlCrSi alloy target is opened again, the power of the TiAlCrSi alloy target remains unchanged, the deposition time is 4min to 6min, and then the TiAlCrSi alloy target is closed.
10. A high-strength, high-conductivity, corrosion-resistant and antibacterial alloy film prepared by the preparation method according to any one of claims 1 to 9, characterized in that: The high-strength, high-conductivity, corrosion-resistant and antibacterial alloy film is a TiAlCrSiAg alloy film.
Citation Information
Patent Citations
Preparation method of titanium alloy surface Ag-doped TiO2 thin film
CN103911593A
Tool with TiAlCrSiN PVD coating
CN104662195A
Corrosion-resistant magnetic FeCoNiCuAl high-entropy alloy film material and preparation process thereof
CN116043139A
Amorphous alloy film and preparation method and application thereof
CN117127149A
High-conductivity and high-strength high-entropy alloy film and preparation method thereof
CN117758127A